Effect Of Health Education On Oral Hygiene On Reducing The Risk Of Caries In Primary School Children - Yuni Astuti; Riama Vensya Sitohang (CV. Get Press Indonesia, 2026)
Health education on oral hygiene plays a crucial role in preventing dental problems, particularly caries, among children. In Indonesia, the prevalence of caries in primary school students remains high, largely due to inadequate understanding of proper oral hygiene practices. This study aimed to evaluate the effect of oral hygiene health education on reducing caries risk in elementary school children. An experimental pretest–posttest design was conducted involving 55 students from SD Negeri 15 Anduring Padang. Data were collected using questionnaires and direct assessments of oral hygiene status and dental caries before and after the health education intervention. Statistical analysis using paired t-tests was applied to determine differences in oral hygiene scores and caries risk following the intervention. The findings demonstrated significant improvements in students’ knowledge and oral hygiene behaviors, accompanied by a substantial decrease in caries risk. The p-value of 0.000 indicated that the educational intervention had a strong positive effect on reducing caries risk. These results emphasize the importance of integrating structured oral hygiene education into the school curriculum and involving both teachers and health professionals in routinely providing information, demonstrations of correct brushing techniques, and guidance on dental health maintenance. Long-term implementation and periodic evaluation of such programs are essential to achieve optimal outcomes and ensure sustainability. In conclusion, health education on oral hygiene effectively reduces caries risk in children and should be consistently implemented as part of routine health promotion activities in primary schools.